Missed Opportunities for HIV Prevention in Perinatal Care Settings in the United States - Pollock, Lealah; Warren, Marliese; Levison, Judy (Frontiers in Reproductive Health, 2021)
Universal opt-out HIV screening in pregnancy is an essential intervention toward eliminating perinatal HIV transmission in the US. However, it fails to identify pregnant people who are HIV negative at the time of testing but are at ongoing risk for HIV acquisition. Those of us involved in caring for women living with HIV are acutely aware of the many diagnoses of HIV that might have been prevented if only a partner had been tested for HIV or preexposure prophylaxis (PrEP) had been offered to a patient. This perspective article will review current recommendations and evidence-based interventions to evaluate missed opportunities for HIV prevention in US perinatal care settings. We identified three barriers to implementation of HIV prevention strategies during pregnancy and breastfeeding: (1) HIV risk for women is underestimated and poorly defined in clinical practice; (2) Partner testing is challenging and implementation studies in the US are lacking; and (3) PrEP remains underutilized. In March 2020, the National Perinatal HIV Hotline convened a group of clinicians and researchers specializing in perinatal HIV care to a case-based discussion of missed opportunities in perinatal HIV prevention. From our review of the literature via PubMed search as well as expert opinions gathered in this discussion, we make recommendations for addressing these barriers.